Review article: Effective management of opioid withdrawal symptoms: A gateway to opioid dependence treatment. Issue 2 (31st January 2019) - Kosten, Thomas R.; Baxter, Louis E.
Abstract : Background and Objectives: The opioid crisis has taken an immense toll in the United States. On average, five lives are lost to an opioid overdose every hour of the day; estimated costs associated with opioid misuse exceed $500 billion annually. Illicit opioid discontinuation is the first step in the treatment of opioid use disorder (OUD), and transition to an opioid agonist may initiate treatment. However, discontinuation to abstinence from either OUD directly or following agonist treatment results in severely distressing opioid withdrawal symptoms (OWS). Methods: This review evaluated studies on the etiology, burden, and management of OWS. Results: Noradrenergic hyperactivity generates many OWS. These OWS can cause patients to relapse during early opioid discontinuation. While agonist therapies are generally first‐line for moderate or severe OUD and reduce OWS, prescribing restrictions can limit their availability. Discussion and Conclusions: Non‐opioid medications to treat OWS provides a gateway into long‐term treatment with naltrexone or psychosocial therapies. For opioid dependent patients without OUD, non‐opioid treatments like α‐2 adrenergic agonists can facilitate opioid tapering. Scientific Significance: For the millions who are physically dependent on opioids, new treatments for OWS can enhance recovery from OUD and prevent relapse. (© 2019 The Authors. The American Journal on Addictions Published by Wiley Periodicals, Inc.;XX:1–8)